Efficacy of pre-emptive peripheral nerve block using 0.25% bupivacaine for postoperative analgesia in patients undergoing maxillofacial surgeries under general anesthesia - Lini Srivastava; Soumyadip Pal; Saikat Majumdar; Soma Chakraborty; Kaushal Kabir; Manabendra Sarkar; Jati Sankar Rudra (Asian Journal of Medical Sciences, 2023)
Background: Conventional analgesia using non-steroidal anti-inflammatory drugs not only provides inadequate pain relief but also can produce a multitude of systemic adverse effects. During oral and maxillofacial surgeries, inhibition of central sensitization by pre-incision nerve blocks with local anesthetic can reduce postoperative pain, may curtail analgesic requirement, and thereby can provide better patient comfort. Aims and Objectives: This study aimed to evaluate the effectiveness of pre-incisional peripheral nerve block using 0.25% bupivacaine over placebo for postoperative pain relief in patients undergoing oral and maxillofacial surgery under general anesthesia. Materials and Methods: One hundred and twenty patients of 18–35 years of either sex, American Society of Anesthesiologists physical status class I and II had undergone oral and maxillofacial surgeries were divided into two groups to receive bupivacaine 0.25% (Study group, n=60) normal saline (Control group, n=60) for nerve block before surgical incision. Postoperative pain was assessed by Visual Analog Scale (VAS) score and verbal response scale (VRS) score. The number of rescue analgesia was required in the first 24 h and the incidence of any complications associated with this agent was documented. Results: The VAS score was found considerably lower in the bupivacaine group compared with the control group in the first 24 h of postoperative period (P<0.05). A similar trend was observed with VRS score in the first 16 h of postoperative period (P<0.05). The number of rescue analgesia required in the control group was much higher in comparison with the study group. There was no serious adverse event in both the groups. Conclusion: Bupivacaine 0.25% as pre-emptive analgesia can be used to reduce postoperative pain and analgesic requirements in maxillofacial surgeries.